Characteristics of soil acidification of haplic Acrisols on ancient alluvial deposits under intensive cassava cultivation in Chau Thanh district, Tay Ninh province - Tho*, Nguyen; Hoa, Nguyen Thi (Vietnam Journal of Earth Sciences, 2017)
This paper clarified the characteristics of soil acidification of haplic Acrisols on ancient alluvial deposit under intensive cassava cultivation in Chau Thanh district, Tay Ninh province, Southeastern Vietnam. Soils were sampled at 3 intervals (0-20, 20-40, 40-60 cm in depth) in 12 sites of intensive cassava cultivation and geochemical parameters related to soil acidity were analysed. The haplic Acrisols under intensive cassava cultivation showed quite high levels of active and exchange acidity (pHH2O 4.40±0.11, pHKCl 3.98±0.07). The hydrolytic acidity and Al saturation level were also high (respectively 4.52±0.37 meq/100g and 57.64±6.41%) while the exchange alkali and alkaline earth cations were very low (Ca2+ 0.76±0.25 meq/100g, Mg2+ 0.88±0.85 meq/100g, K+ 0.16±0.06 meq/100g in the top layer). This exhibited a limit for mineral nutrients and risk of Al toxicity to cassava plants. If the area for intensive cassava cultivation is expanded and the high-yield cassava varieties are applied, the risk of soil acidification will be expected to be highly serious. It is needed to clarify the processes involved and to establish measures to reduce soil acidification and stabilize cassava production in the study area and Tay Ninh province.References Araki S., Sarr P.S., 2013. The Effect of Cassava Cultivation on Soil Acidification.Center for African Area Studies, Kyoto University, Japan.A Report on Cassava Science day, IITA Cameroon February 18, 32-36. CIAT, 1979. Annual Report for 1978.CIAT, cassava programme, Cali, Colombia, pp.A76-84. In: Hillocks R.J., Thresh J.M., Bellotti A.C. (Eds.), Cassava: Biology, Production, and Utilization. CABI Publishing, USA, ISBN 0-85199-524-1. CIAT, 2007. Cassava Research and Development in Asia: Exploring New Opportunities for an Ancient Crop. Proceedings of the seven Regional Workshop in Bangkok, Thailand, Oct 28-Nov 1, 2002. Centro Internacional de Agricultura Tropical, pp.668. Dolui A.K., Mehta S., 2001. Forms of acidity and lime requirement of some Alfisols.Agropedology 11, 71-77. Dowuona G.N.N., Atwere P., Dubbin W., Nude P.M., Mutala B.E., Nartey E.K., Heck R.J., 2012. Characteristics of termite mounds and associated acrisols in the coastal savanna zone of Ghana and impact on hydraulic conductivity. Natural Science 4(7), 423-437. Francis N.A., Constant A.M.F., Ijang T.P., Atanga N.S., Clarisse M.M.Y., DelphineM-L., Simon N.T., 2013. Effects of Cassava Cultivation on Soil Quality Indicators in the Humid Forest Zone of Cameroon.Greener Journal of Agricultural Sciences 3(6), 451-457. Gasior J., Puchalski C., 2010. Effects of potassium on the dynamics of chemical elements in brown soil reconstructed profile. Short Communication.Polish Journal of Environmental Studies 20(3), 789-794. Howeler R.H., 1996. Mineral nutrition of cassava. In: Craswell, E.T., C.J. Asher and J.N. O’Sullivan (Eds.), Mineral nutrient disorder of root crops in the Pacific. Proceedings of workshop, Nuku’alofa, Kingdom of Tonga, 17-20 April 1995. ACIAR Proceedings 65, 110-116. Howeler, R.H. and Phien, T., 2000. Integrated nutrient management for more sustainable cassava production in Vietnam. Proceedings of the Vietnamese Cassava Workshop on Progress in Cassava Research and Extension in Vietnam, 16-18 March 1999, Ho Chi Minh city, Vietnam, 12-54. Howeler RH., 2001. Nutrient Inputs and Losses in Cassava-based Cropping Systems-Examples from Vietnam and Thailand. International Workshop on Nutrient Balances for Sustainable Agricultural Production and Natural Resource Management in Southeast Asia. Bangkok, Thailand, 20-22. Juo A.S.R., Franzluebbers K., 2003. Tropical Soils: Properties and Management for Sustainable Agriculture. Oxford University Press, UK, ISBN-10: 0-19-511598-8, pp.304. Kamprath E., 1980. Soil acidity in well-drained soils of the tropics. In: Juo A.S.R., Franzluebbers K. (Eds.), Tropical Soils: Properties and Management for Sustainable Agriculture, Oxford University Press, New York, USA, ISBN: 0-19-511598-8, pp.283. Le Cong Nong, 2010. Study and assess the current conditions, build up the pedological map and provide solutions to reclaim soils in the Seedling Production Facility of Trang Bang -Tay Ninh. Research Institute for oil and oil plants. Le Huy Ham, Hoang Kim, Nguyen Thi Truc Mai, Nguyen Bach Mai and Reinhardt Howeler, 2016. The cassava revolution in Vietnam. World Congress on root and tuber crops. Nanning Guangxi, China 18-22 Jan 2016.Mekaru T., Uehara G., 1972. Anion Adsorption in Ferruginous Tropical Soils.Soil Science Society of America Journal 36(2), 296-300.Nguyen Tu Siem, Thai Phien, 1993. Effect of cultivation for soil erosion control and fertilization to soil conservation and crop yields on sloping land. Highlight of research results on science and technology of agriculture. In: Howeler R.H,Phien T. (Eds.), Integrated nutrient management for more sustainable cassava production in Vietnam.http://ciatlibrary.ciat.cgiar.org/Articulos_Ciat/00113_Integrated_Nutrient_Management.pdf. Noble A., Ruaysoongnern S., Sukchan S., Berthelsen S., 2004. Role of soil resource data in assessing soil acidification risk: an example from Northeast Thailand. In: Eswaran H., Vijarnsorn P., Vearasilp T.,Padmanabhan E. (Eds.), Innovative techniques in soil survey: developing the foundation for a new generation of soil resource inventories and their utilization. Proceedings of a conference, Cha-am, Thailand, 21-26 March 2004, 333-340. Pham Van Bien, Hoang Kim, Tran Ngoc Ngoan, Howeler, RH., and Wang, J.J., 2002. New developments in the cassava sector of Vietnam. www.ciat. cgiar.org/asia_cassava/. Rengel Z., 2005. Handbook of Soil acidity. Marcel Dekker, Inc, New York, ISBN 0-8247-0890-3, pp.511. Rowell D.L., 1994. Soil Science: Methods and Applications. Department of Soil Science, University of Reading, Pearson Education, Prentice Hall, Harlow, UK, ISBN 0-582-08784-8, pp.345. Sanginga N., Woomer P.L., 2009. Integrated Soil fertility management in Africa: Principles, Practices and Developmental Process. Tropical Soil Biology and Fertility Institute of the International Centre for Tropical Agriculture (TSBF-CIAT), ISBN 978-92-9059-261-7, pp.263. Sarr P.S., Araki S., Njukwe E., 2013. Sequential cultivation of cassava varieties in eastern Cameroon: effects on production and soil status. A Report on Cassava Science Day: Cassava performance under different soil management, IITA, Cameroon, Feb. 18, 2013, pp.4-5. Sat C.D., Deturck P., 1998. Cassava soils and nutrient management in South Vietnam.In Howeler R.H. (Eds.), Cassava breeding, agronomy and farmer participatory research in Asia. Proc. 5th Regional Workshop, Danzhou, Hainan, China. Nov 3-8, 1996, 257-267. Šimanský V., 2011. Chemical properties, soil structure and organic matter in different soil managements and their relationships with carbon sequestration in water-stable aggregates. Research Journal of Agricultural Science 43(4), 138-149. Soils and Fertilizers Research Institute, 1998. Handbook for the analysis of Soil, Water, Fertilizer, and Plants. Agricultural Publishing House, 595pp. StatSoft, Inc., 2001. STATISTICA (Data AnalysisSoftware System), Version 7.www.statsoft.com. Sub-NIAPP, 2004. Report on Tay Ninh soil map. Ministry of Agriculture and Rural Development. Supriyo H., Matsue N., Yoshinaga N., 1992. Chemistry and Mineralogy of Some Soils from Indonesia.Soil Science and Plant Nutrition 38(2), 217-225. Suyamto H., 1998. Better Crops International 12(2), 12-13. Tay Ninh Provincial People’s Committee, 2012. Decision No.44 of Tay Ninh Provincial People’s Committee. Quyet-dinh-44-2012-QD-UBND-Quy-hoach-phat-trien-nong-nghiep-tinh-Tay-Ninh-152762.aspx. Zołotajkin M., Ciba J., Kluczka J., Skwira M., Smoliński A., 2011. Exchangeable and Bioavailable Aluminium in the Mountain Forest Soil of BaraniaGóra Range (Silesian Beskids, Poland). Water, Air, Soil Pollution (216), 571-580.